(untitled) (European Journal of Behavioral Sciences, 2020)
Television series are among the most important television products and are indispensable as prime-time representatives of a broadcast generation that international television channels put a strong emphasis on. Both the quality of the content and the cultural similarities the audience perceives in the story carry relevance in terms of reaching the target audience. This study aims to deal with the development of the TV series sector in the context of Turkish TV series (TTS) in recent years, regarding the export of these series abroad and the sociological and cultural effects of these series in the countries they are shown. The study explores the viewing habits of Croatian viewers, their perspective on television watching, TV series in general, their experience with different TV series and the elements that drew them to continue watching, and their opinion on TV series imported from North America, Latin America, and Europe. The study tries to understand the audience’s perspectives on Turkish TV series and how they shape their preferences. This study also presents the number of Turkish TV series released in Croatia between 2010 (when the first Turkish TV series was released in Croatia) and 2020 and their effects on local people. Turkish TV series, production details, and broadcasting info were analyzed and explained using information obtained from the Croatian audience through an online questionnaire.